Effect of Nitrogen and Humic Acid on Growth and Yield of Pakcoy (Brassica rapa subsp. chinensis) Plants - Pamungkas, Panji; Anwar Hidayat, Yayat Nur; Wijaya (Jurnal Agrosci, 2024)
Decreased soil quality due to reduced nutrient content is one of the causes of decreasedquality and yield in plants. The use of humic acid organic matter with N fertilizer is one of the effortsto increase nutrients in the soil while increasing plant growth and yield. This research was conductedin Heuleut Village, Leuwimunding District, Majalengka Regency, from May to June 2024. Theresearch method used was the experimental method with a group-randomized design. The treatmentconsisted of 16 treatments that were repeated twice. The variables observed were plant height,number of leaves, root volume, plant fresh weight, leaf area, and plant growth rate. The resultsshowed that the use of N fertilizer at a dose of 115 kg/ha (urea 250 kg/ha) and humic acid 3 g/planthad a good effect on all variables observed. The results of soil analysis showed an increase in N-totaland C-organic.